Words with wings - Grimes, Nikki (Honesdale, Pa. : Wordsong, an imprint of Highlights, 2013)
Gabby daydreams to tune out her parents' arguments, but when her parents' divorce, and she begins a new school, daydreaming gets her into trouble. Her mother scolds her for it, her teacher keeps telling her to pay attention, and the other kids tease her. Until she finds a friend who also daydreams and her teacher decides to work a daydreaming-writing session into every school day. With a notebook "thick with daydreams," Gabby grows more confident about herself and her future.
School Library Journal, November 2013
Booklist starred, September 2013
Publisher's Weekly, August 2013
Kirkus Starred, August 2013
4.3
3-6
Keywords: Writing -- Juvenile fiction; Imagination -- Juvenile fiction; Families -- Juvenile fiction; Writing -- Fiction; Imagination -- Fiction; Family life -- Fiction; Novels in verse; Writing -- Fiction; Imagination -- Fiction; Family life -- Fiction; Novels in verse; Novels in verse